2008
DOI: 10.1083/jcb.200712101
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nucleoids maintain genetic autonomy but allow for functional complementation

Abstract: Mitochondrial DNA (mtDNA) is packaged into DNA-protein assemblies called nucleoids, but the mode of mtDNA propagation via the nucleoid remains controversial. Two mechanisms have been proposed: nucleoids may consistently maintain their mtDNA content faithfully, or nucleoids may exchange mtDNAs dynamically. To test these models directly, two cell lines were fused, each homoplasmic for a partially deleted mtDNA in which the deletions were nonoverlapping and each deficient in mitochondrial protein synthesis, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
139
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 41 publications
11
139
2
Order By: Relevance
“…This finding means that the majority of the nucleoids just contain a single copy of mtDNA. This arrangement is consistent with the so-called "faithful" nucleoid model (34), whereby nucleoids as a general rule do not exchange genomes with each other.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding means that the majority of the nucleoids just contain a single copy of mtDNA. This arrangement is consistent with the so-called "faithful" nucleoid model (34), whereby nucleoids as a general rule do not exchange genomes with each other.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that each nucleoid contains on average 6 to 10 copies (29), 2 to 8 copies (19), or ∼5 copies of mtDNA (34). We used confocal microscopy analyses and qPCR determination of mtDNA copy number and found on average ∼2.3 mtDNA molecules per nucleoid in human fibroblasts.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, a partner protein, post-translational modification or cofactor might enable TEFM to resolve recombination junctions. Intramolecular DNA recombination in mitochondria depends on the host cell or tissue expressing the relevant apparatus and targeting it to the organelles, but intermolecular mtDNA recombination requires the physical interaction of discrete molecules, and this occurred only rarely in one human cell line studied [37]. Moreover, in a laboratory strain of mice there was no evidence of intermolecular mtDNA recombination in the germ-line over the course of 50 generations [42].…”
Section: The Machinery Of Mtdna Selectionmentioning
confidence: 99%
“…This implies interconnections between nucleoids, which might for example be ATAD3-dependent (see [36] and the following section). Nevertheless, physically, nucleoids rarely interact [37], perhaps to prevent defective mtDNA variants piggybacking on nucleoids containing wild-type mtDNA. The system maintaining stable heteroplasmy may fail, or be suspended in some circumstances [38], and while the consequences can be devastating for the affected individuals, it does so only rarely, and so is advantageous to the human population as a whole.…”
Section: Stable Heteroplasmy: the Persistence Of A Fixed Proportion Omentioning
confidence: 99%
“…1). The mixing of the matrix content of a few damaged mitochondria with the larger matrix pool of the intact mitochondrial network potentially allows an efficient complementation of biomolecules (26). Therefore, effective mitochondrial ''content mixing'' is able to reduce the deleterious effects of damaged proteins and RNAs and mutated mitochondrial DNAs (mtDNAs) (13,14,25).…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%